Comprehensive analysis of the papillary thyroid carcinoma identifies CSGALNACT1 as a proliferation driver and prognostic biomarker - Zhao, Yu; Zhang, Juan; Yao, Yong; Yu, Linna (Frontiers in Cell and Developmental Biology, 2025)
Papillary thyroid carcinoma (PTC) is the most prevalent form of thyroid cancer, yet its cellular heterogeneity and prognostic determinants remain poorly defined. Here, we integrate two single-cell RNA sequencing datasets comprising 20 human thyroid samples to construct a high-resolution cellular atlas of PTC. We identify 29 distinct cellular subpopulations and delineate their composition, dynamics, and interactions in healthy versus tumor tissues. Notably, epithelial and monocyte populations were markedly expanded in PTC, whereas adaptive immune subsets such as B and T cells were diminished. Cell–cell communication analysis revealed enhanced intercellular signaling in the tumor microenvironment, with epithelial and endothelial cells receiving the strongest inputs. Among monocyte-specific transcriptional signatures, we identified 65 prognostic genes via univariate Cox analysis. A LASSO-derived 14-gene risk score robustly stratified patient outcomes, with CSGALNACT1 emerging as a key epithelial-specific, independent prognostic gene. Pseudotime analysis further supported its role in epithelial cell differentiation. Functional validation demonstrated that CSGALNACT1 promotes proliferation in PTC cell lines, suggesting a potential oncogenic function. Immune deconvolution across risk groups revealed substantial divergence in innate and adaptive immune infiltration, indicating a close interplay between tumor-intrinsic transcriptional programs and immune microenvironment remodeling. Collectively, our study provides a comprehensive single-cell framework for PTC, identifies a clinically relevant risk model, and highlights CSGALNACT1 as a potential therapeutic target.